2006
DOI: 10.1177/1359105306066643
|View full text |Cite
|
Sign up to set email alerts
|

What is Good Qualitative Research?

Abstract: Qualitative research has an enormous amount to contribute to the fields of health, medicine and public health but readers and reviewers from these fields have little understanding of how to judge its quality. Work to date accurately reflects the complexity of the theoretical debate required but may not meet the needs of practitioners attempting to apply qualitative work in reviews of evidence. This article describes a simple, practitioner-focused framework for assessing the rigour of qualitative research that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
104
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(108 citation statements)
references
References 23 publications
0
104
0
4
Order By: Relevance
“…A study by Armstrong et al (1997) provided only partial support for inter-coder reliability and found that although coders identified similar themes, they organized and labelled them differently. Many advocate that the adherence to systematic and thorough analytical processes, together with providing a high level of transparency, is sufficient to ensure rigour (Elliott et al 1999;Meyrick 2006;Yardley 2000). Accordingly, we argue that the steps taken to ensure quality and transparency in this study contribute to a satisfactory level of rigour.…”
Section: Methodological Considerations and Limitationsmentioning
confidence: 78%
See 1 more Smart Citation
“…A study by Armstrong et al (1997) provided only partial support for inter-coder reliability and found that although coders identified similar themes, they organized and labelled them differently. Many advocate that the adherence to systematic and thorough analytical processes, together with providing a high level of transparency, is sufficient to ensure rigour (Elliott et al 1999;Meyrick 2006;Yardley 2000). Accordingly, we argue that the steps taken to ensure quality and transparency in this study contribute to a satisfactory level of rigour.…”
Section: Methodological Considerations and Limitationsmentioning
confidence: 78%
“…In qualitative inquiry, making explicit ones philosophical stance is important to ensure transparency (Meyrick 2006). Philosophical framework has important implications for the research focus and design, as well as the interpretations of findings.…”
Section: Methodsmentioning
confidence: 99%
“…É sabido que as pesquisas qualitativas compõem uma pletora, nem sempre convergente, de posições ontológicas, epistemológicas e metodológicas (Ballinger, 2004;EasterbySmith, Golden-Biddle, & Locke, 2008;Goertz & Mahoney, 2012;Krefting, 1991;Kuper, Lingard, & Levinson, 2008;Meyrick, 2006;Pratt, 2008). Dessa maneira, os interessados em realizar um estudo qualitativo devem primeiramente declarar essas posições.…”
Section: A Filosofia De Deleuze E Os Estudos Organizacionaisunclassified
“…The research team addressed rigour within the research process with attention to the two key principles proposed in Meyrick's [37] model: transparency about the research process and the use of a systematic approach. A reflexive diary and an audit trail were maintained throughout the research process, and detailed the decisions made during data collection and analysis.…”
Section: Rigourmentioning
confidence: 99%